Self Storage: A Contemporary Archaeology of Domestic Interiority - Filippides, Emma (UI Scholars Hub, 2019)
This architectural historical study aims to interrogate rituals of contemporary inhabitation in the United Kingdom by tracing the rise of the self storage facility. While the proliferation of domestic self storage in the UK is derived from a web of correlations, this research considers self storage as a lens through which the subjective experience of inhabiting the neoliberal city, may be understood. Drawing from archaeological methods to conduct a material study of the contents of abandoned storage units, this study engages specifically with self storage as a long-term solution to domestic storage inadequacies. The material and theoretical engagements of this research raise three interpretations of the architecture of self storage and the material contents kept within, as situated in relation to domestic interiority. Pertaining respectively to excessive accumulation, intergenerational transference and emotional deferral; this research seeks to understand the span of motivations behind the depositing of domestic contents to self storage, thus exploring the psychic relationships inhabitants construct in response to this extended spatiality of the home’s contents. Articulating a meeting point between the economic and the existential, this research presents modern forms of self storage as a deeply metaphorical spatial phenomenon which is able to produce a reading of contemporary patterns in an urban and suburban dwelling.